Confirmation of the Effectiveness and Genetic Positions of Disease Resistance Loci in ‘Kishmish Vatkana’ (Ren1) and ‘Villard Blanc’ (Ren3 and Rpv3) - Veikondis, R.; Burger, P.; Vermeulen, A.; Van Heerden, C.J.; Prins, R. (South African Journal of Enology and Viticulture, 2018)
This study aimed to validate the effectiveness and to genetically characterise the fungal disease resistance genes of ‘Kishmish Vatkana’ and ‘Villard Blanc’ in South Africa using microsatellite (SSR) markers and a Quantitative Trait Loci (QTL) approach. An F1 ‘Sunred Seedless’ × ‘Kishmish Vatkana’ cross was used to generate a partial linkage map for chromosome 13 known to harbour the Ren1 powdery mildew locus of ‘Kishmish Vatkana’. The effectiveness of this locus was validated, explaining between 44.8% and 57.7% of the observed phenotypic variance. An F1 ‘Villard Blanc’ × ‘G1-6604’ cross was used to generate partial linkage maps for chromosomes 15 and 18, reported to harbour fungal resistance genes of ‘Villard Blanc’. The powdery mildew QTL (Ren3) was validated on chromosome 15 of ‘Villard Blanc’, which explained between 18.9% and 23.9% of the phenotypic variance observed. The downy mildew resistance QTL on chromosome 18 (Rpv3) of ‘Villard Blanc’ was also confirmed, and it explained between 19.1% and 21.2% of the phenotypic variance observed. This molecular information and individual sources of resistance have already been implemented in the marker-assisted selection (MAS) and gene pyramiding efforts of the table grape breeding program of the Agricultural Research Council (ARC) Infruitec-Nietvoorbij.